26.1k views
4 votes
Find the H.C.F of the following expressions.{x²-3x,x²-9}​

User Tssch
by
5.1k points

2 Answers

7 votes

Answer:

Explanation:

x2−3x+2=x2−2x−x+2

x(x−2)−1(x−2)=(x−2)(x−1)

Now

x2−4x+3=x2−3x−x+3

x(x−3)−1(x−3)=(x−3)(x−1)

Thus, the only common factor is (x-1)

Option A

hope it helps

User PhonicUK
by
4.7k points
4 votes

Answer:

x2−3x+2=x2−2x−x+2

x(x−2)−1(x−2)=(x−2)(x−1)

Now

x2−4x+3=x2−3x−x+3

x(x−3)−1(x−3)=(x−3)(x−1)

Thus, the only common factor is (x-1)

Option A

hiiiii

User Rohit Jagtap
by
5.3k points